Relationship between family meals away from home and nutritional status of adolescents - Jetan, Cynthia; Mohd Shariff, Zalilah; Lim, Mei Yee (Nutrition Society of Malaysia, 2013)
Introduction: Despite the many benefits of family meals, data on association between family meals away from home (FMAFH) and nutritional status of adolescents is limited. This study determined the association between FMAFH with dietary intake and body mass index of adolescents (N=408). Methods: Data were obtained through interviewer-administered questionnaire and anthropometric measurements of adolescents. Results: Respondents comprised 53.7% females, 67.6% Chinese with the mean age of sample being 13.7 ± 0.6 years old. Generally, male adolescents had higher intakes of energy, macronutrients and micronutrients. All nutrients except calcium (51.3%), iron (females - 54.7%) and vitamin A (females - 86.1%) met the recommended intakes. A higher proportion of male (25.4%) than female (13.6%) adolescents were overweight and obese. About 44% of respondents had family meals ≥ 7 times in the previous week with 48.9% reported having family meals at home ≥ 7 times weekly. The majority (91.2%) of adolescents had FMAFH at least once a week either at restaurants (53%), fast food outlets (41.6%), food courts in shopping complexes (40%) or food stalls (30.2%). As the frequency of FMAFH increased, there was an increasing trend in energy and energy-adjusted nutrient intakes. However, only energy-adjusted fat intake was significantly high (p<0.05) in adolescents having FMAFH > 7 times weekly. No significant association was observed for frequency of FMAFH and body mass index. Conclusion: With increasing dependence on foods outside the home, FMAFH can be a source of healthy diet for families provided they have the knowledge, skills and motivation to make healthy food choices.